PSIII-4 Late-Breaking: Genetic Marker Association Study of Heifer Pregnancy in Red Angus Cattle. (22nd October 2022) - Saad, Hamad M; Gonzalez-Berrios, Carolina L; Speidel, Scott E; Enns, R Mark; Boldt, Ryan J; Hansen, Thomas R R; Thomas, Milt G
Abstract: Heifer pregnancy (HPG) is lowly heritable, yet economically relevant in beef cattle production systems. Hence, identifying single nucleotide polymorphisms (SNP) associated with phenotype could increase the amount of information used in the genetic evaluation of the trait. Using RNA-sequence data from lactating Holstein cows, a set of SNP (n = 69) were discovered among embryo mortality conceptuses (Conceptus-SNP) associated with maternal recognition of pregnancy on day 16 after artificial insemination (AI). To further study these SNP, our objective was to conduct analyses to identify markers associated with HPG in Red Angus. Phenotypic records and genotypes were provided by the Red Angus Association of America (RAAA). For phenotypes, a total of 59, 387 cattle records, from the June 2022 RAAA genetic evaluation, were used in the analysis. For genotype data, a 47, 860 SNP panel (excluding SNP on the X-chromosome) were formed by combining the historical RAAA genotype data (96, 162 animals with genotypes) and genotypes from whole genome sequence of 30 prominent Red Angus AI sires. Markers were mapped to the ARS-UCD1.2 bovine reference genome and then imputed to 47, 860 SNP panel using findhap software. A subset of SNP (n = 2, 169 SNP; Conceptus-SNP and the multi-breed selected reduced panel [MSRP]) were extracted from the imputed genotypes file. Using PLINK software, genotype quality control procedure was performed so that animals with call rate < 0.9 were removed. A marker was removed if: it had minor allele frequency < 0.01, not in Hardy–Weinberg equilibrium (P < 0.00001), or in high linkage disequilibrium (r2 > 0.95). The final genotype file contained 96, 667 animals with 2, 137 SNP. A Bayes Cπ single-step super hybrid model (π = 0.99), using the BOLT software package, was used to estimate marker's posterior probability of inclusion (PPI), the marker significance criterion in predicting HPG. A marker's PPI was calculated as the average probability from four different Gibbs sampling chains of 75, 000 iterations that included 5, 000 iterations as burn-in. Markers rs42576394 (18:60583784) and rs42942055 (14:34249373) had PPI of 25.5 and 7.1%, respectively; suggesting association with HPG. None of the Conceptus-SNP had a detectable association with HPG; however, these Conceptus-SNP may be much more informative for genotype to phenotype association analyses for the trait of stayability. Such a trait would be measured with lactating mature beef cows and potentially more similar to the lactating Holstein cows from which the markers were discovered.